Planning and implementation of holistic-integrative early childhood education management for achieving quality services - Amrindono Amrindono; Achmad Fadlan; Nurlinda Nurlinda; Atika Wirdasari; Kompri Kompri (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze the planning and implementation of Holistic Integrative Early Childhood Education (HI-ECE) management in achieving quality services. A qualitative approach was applied using a case study method in three ECE institutions that have implemented HI-ECE. Data were collected through in-depth interviews, participatory observation, and document review, then analyzed using Miles and Huberman’s interactive analysis model. The findings reveal that during the planning stage, the institutions designed programs based on children’s needs assessment covering education, health, nutrition, and protection aspects, involving multi-sector stakeholders. In the implementation stage, strategies included thematic curriculum integration, regular health services, provision of nutritious meals, strengthening parental involvement, and coordination with community health centers, social services, and community organizations. However, challenges were identified, such as limited funding, lack of specialized personnel, and coordination difficulties among agencies. Improvement efforts were made through teacher capacity building, partnership strengthening, and utilization of local resources. This study highlights that the success of HI-ECE management in achieving quality services greatly depends on participatory planning, integrated implementation, and continuous support from all stakeholders.